2015
DOI: 10.1016/j.jval.2015.03.1041
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of age-related Macular degeneration in Indian Population: a systematic review

Abstract: costs, we assumed that a treatment was provided to every patient who visited the dentist according to the national dental cavities guideline, all related costs were obtained from the SOAT fare manual 2011 reported by the government. We multiplied the treatment cost for each patient by the total number of dental visits to obtain the third-payer cost. We calculated from the patient´s perspective the lost output as a result of a reduction of productivity due to dental cavities, using DALYs, multiplied by the 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…In India, the prevalence of AMD ranges from 1.4 to 3.1%, with the most common demographic factor affecting the prevalence of AMD being advanced age (> 65 years) [ 5 ]. The global prevalence of any AMD within an age range of 45 to 85 years was 8.7% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India, the prevalence of AMD ranges from 1.4 to 3.1%, with the most common demographic factor affecting the prevalence of AMD being advanced age (> 65 years) [ 5 ]. The global prevalence of any AMD within an age range of 45 to 85 years was 8.7% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neovascular vessels proliferate underneath the retinal pigment epithelium, and leakage from these vessels leads to retinal elevation resulting in blurring of vision [ 2 , 3 ]. In India, the prevalence of AMD is estimated between 1.4% and 3.1% with advanced age (> 65 years) being the most common factor affecting the prevalence of AMD [ 4 ]. The global prevalence of AMD is estimated at ~ 8.7% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the ailment affects more females (2.5%) than males (1.9%) in the age group above 65. 2 In this study, we propose an innovative approach to create a model to enhance drusen features in retinal fundus images. The approach is trustable to a higher degree by validating on two databases.…”
Section: Introductionmentioning
confidence: 99%